Navigating Threshold Concepts and Learning Outcomes in Counselling and Psychotherapy Training: An existential paradox (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Aspects of educational theory are employed to explore the concepts that students must navigate when studying counselling and psychotherapy. Assessment and evaluation strategies are considered in relation to the phenomenological exploration of life worlds, in a not-knowing approach. Attention is paid to issues of diversity, inclusion and exclusion.
Keywords: Teaching; phenomenological; existential; Threshold-Concepts; taxonomy- matrix; diversity